The English Church Women's Association (ECWA) : Empowering towards partnership in mission or entrenching gender inequality? : The case of St Mary's Anglican Church on-the-Braak, Stellenbosch 1875-2015 - Pembamoyo, Eston Dickson (Stellenbosch : Stellenbosch University, 2017)
Thesis (MTh)--Stellenbosch University, 2017.